Обрыв: Роман в 6-ти ч. / И. А. Гончаров - Гончаров Иван Александрович (Сов. Россия, 1984)
Экземпляры: Аб (20121005) / Инвентарный номер: 98919 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: Г 65 / ББК: 84(2Рос=Рус)1